Antecedent interventions for pediatric feeding problems. Issue 2 (17th April 2014) - Seubert, Christine; Fryling, Mitch J.; Wallace, Michele D.; Jiminez, Agustin R.; Meier, Aimee E.
<x xml:space="preserve">Abstract</x> Behavior analysts have implemented and evaluated several antecedent strategies for treating pediatric feeding problems. The extent to which antecedent interventions are beneficial, however, is not yet clear. This review examines recent research in the Journal of Applied Behavior Analysis (2000–2012) that evaluated antecedent interventions. We found that the feeding diagnosis (food refusal vs. food selectivity) and presence of feeding‐related medical conditions were related to the differential implementation of antecedent interventions.